Green Transformation and Its Impact on Employee Green Performance in the Logistics Industry in Indonesia - Erni Pratiwi Perwitasari; Lim Sanny; Zaenal Abidin; Mustika Sari (Annals of Human Resource Management Research, 2026)
Purpose: This study examines the impact of green human resources management (GHRM), green innovation, and green transformational leadership on employee green performance through green work engagement in logistics companies in Indonesia. Research Methodology: A quantitative approach was used, with a 1–5 Likert scale questionnaire distributed to 95 respondents, and data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). Results: The results show that GHRM and green transformational leadership have a positive and significant effect on green work engagement, which in turn significantly enhances employee green performance. However, green innovation did not show a significant effect on either green work engagement or employee green performance, either directly or indirectly. The conclusions suggest that logistics companies should focus on strengthening GHRM and green transformational leadership to improve employee engagement and green performance. Conclusions: This study shows that GHRM and Green Transformational Leadership improve employee green performance through green work engagement, while green innovation had no significant effect. The findings suggest prioritizing GHRM and leadership, though the small sample limits generalizability. Limitations: The study's limitations include the relatively small sample size, which limits generalizability to other industries and regions. Contributions: This research contributes to the literature by integrating GHRM, green innovation, and green transformational leadership into a model examining their effects on employee green performance through green work engagement.